2009
DOI: 10.1371/journal.pone.0004840
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility for Superinfection with Streptococcus pneumoniae during Influenza Virus Infection Is Not Caused by TLR7-Mediated Lymphopenia

Abstract: Influenza A virus (IAV) causes respiratory tract infections leading to recurring epidemics with high rates of morbidity and mortality. In the past century IAV induced several world-wide pandemics, the most aggressive occurring in 1918 with a death toll of 20–50 million cases. However, infection with IAV alone is rarely fatal. Instead, death associated with IAV is usually mediated by superinfection with bacteria, mainly Streptococcus pneumoniae. The reasons for this increased susceptibility to bacterial superin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 44 publications
3
52
0
1
Order By: Relevance
“…Furthermore, neutrophil entry into sinuses was blocked (supplemental Video 5). In contrast to the depleting anti-Gr-1 antibody RB6-8C5, 23 the Cxcr2 antiserum did not deplete neutrophils from the BM (supplemental Figure 3). Thus, the induced release of Cxcr2-binding chemokines by G-CSF provides a selective trigger for enhanced motility of neutrophils in the BM, which is a prerequisite for their mobilization into local sinuses and the circulation.…”
Section: G-csf-triggered Release Of Cxcr2 Ligands Mediates Mobilizationmentioning
confidence: 84%
“…Furthermore, neutrophil entry into sinuses was blocked (supplemental Video 5). In contrast to the depleting anti-Gr-1 antibody RB6-8C5, 23 the Cxcr2 antiserum did not deplete neutrophils from the BM (supplemental Figure 3). Thus, the induced release of Cxcr2-binding chemokines by G-CSF provides a selective trigger for enhanced motility of neutrophils in the BM, which is a prerequisite for their mobilization into local sinuses and the circulation.…”
Section: G-csf-triggered Release Of Cxcr2 Ligands Mediates Mobilizationmentioning
confidence: 84%
“…First, we characterized the infection with these strains alone as a reference for coinfection. We used the highly invasive strain TIGR4 (T4) of serotype 4 (27), an invasive strain of serotype 7F, and a carrier strain of serotype 19F (29). According to previous reports, serotype 4 and serotype 7F harbor a high invasive disease potential while serotype 19F is less invasive (30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…At KI, the blood agar plates and THY medium were produced by the Karolinska Microbiology Laboratory (Solna, Sweden). For viral challenges, influenza A/PR/8/34 virus (H1N1; PR8) was produced in Madin-Darby canine kidney (MDCK) cells as described previously (27). The 50% tissue culture infectious dose (TCID 50 ) of the viral stock was determined by incubating 10-fold dilutions of virus stock solution on MDCK cells cultured in Dulbecco's modified Eagle medium (DMEM; Life Technologies, Germany) supplemented with 0.0002% trypsin (Sigma-Aldrich, Germany) and 1% penicillin-streptomycin (ThermoFisher, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One theory proposes that the respiratory epithelial surface is damaged during influenza virus infection and that the exposure of new binding partners, such as platelet-activating factor receptor, enhanced bacterial adherence and growth in the respiratory tract (2,22,34,50). Another theory suggested that the production of a variety of different cellular mediators during influenza virus infection affected the recruitment and function of effector leukocytes, such as neutrophils, in response to a secondary bacterial infection (20,23,39,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%